2001
DOI: 10.1177/014920630102700406
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and consequences of employee displayed positive emotions

Abstract: This study examined whether the psychological climate for service friendliness correlated positively with employee displayed positive emotions, and whether such positive emotional displays influenced customer purchase decision and customer reactions concerning an organization. Data were collected from 290 sales clerks in 156 retail shoe stores in Taiwan, and from 284 customers who were served by one of the sales clerks. Results indicated a positive relationship between psychological climate for service friendl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(246 citation statements)
references
References 40 publications
6
232
0
8
Order By: Relevance
“…In line with previous studies on the role of emotional contagion between employees and customers during service encounters and the impact of emotional contagion processes on service quality (e.g., Barger & Grandey, 2006;Tsai, 2001;Tsai & Huang, 2002), our findings suggest that employees' negative (re)actions are perceived as inappropriate or unfair by customers, thus determining their attitudes (i.e., low service quality). This is again in line with SIP theory (Salancik & Pfeffer, 1978) as employees, through their negative reactions, give social signals to customers and determine their attitudes.…”
Section: Theoretical Contributionssupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous studies on the role of emotional contagion between employees and customers during service encounters and the impact of emotional contagion processes on service quality (e.g., Barger & Grandey, 2006;Tsai, 2001;Tsai & Huang, 2002), our findings suggest that employees' negative (re)actions are perceived as inappropriate or unfair by customers, thus determining their attitudes (i.e., low service quality). This is again in line with SIP theory (Salancik & Pfeffer, 1978) as employees, through their negative reactions, give social signals to customers and determine their attitudes.…”
Section: Theoretical Contributionssupporting
confidence: 91%
“…Past research has shown that employee affective expressions in service contexts shape customer satisfaction with the provided service. For instance, Tsai (2001) showed that positive emotional displays from employees increased customer willingness to return to the store and to speak positively about the provided services to their friends (see also, Tsai & Huang, 2002). Similarly, Pugh (2001) found that observed emotional displays by employees (i.e., greeting, smiling, making eye contact, and thanking the customer) related positively to customer evaluations of service quality.…”
Section: Negative (Re)actionsmentioning
confidence: 95%
See 1 more Smart Citation
“…In this case, employees would display more positive emotions towards customers and other stakeholders. According to Tsai (2001), managers can favour the creation of such a climate implementing human resources practices (e.g. evaluating the appropriateness emotions and giving rewards or punishments accordingly) and removing obstacles to employees displaying positive emotions (e.g.…”
Section: The Logic Of Gift and The Relationship Between Organizationsmentioning
confidence: 99%
“…There are also new trends emerging (Holt, 1997;Tang et al, 2013) that take into account different meanings and the value of feelings and emotional experience as influencing a wide range of consumer attitudes. These include the idea of service quality (Chebat et al, 1995), loyalty to the product (Tsai, 2001), idea of a real provision of services (Gountas et al, 2007), customer satisfaction (Giardini and Frese, 2008;Kaltcheva and Parasuraman, 2009) and future intentions (Martin et al, 2008).…”
Section: Figure 1 Customizing the Market Offermentioning
confidence: 99%